Motivasi Dalam Pembelajaran Bahasa Inggris: Studi Kasus Pada Mahasiswa Jurusan Pendidikan Bahasa Inggris IAIN Surakarta - Rochmat Budi Santosa (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2017)
This study aims at describing how social and cultural motivations of students in choosing the English Department of IAIN Surakarta for their academic and career objectives, how the responses of students to the lecturers in teaching, and how the attitude of the students towards the course they follow.This is a survey research by distributing a questionnaire adapted from Attitude Motivation Test Battery (AMTB) and completed by interview. Data was analyzed by quantitative and descriptive manner. Based on the research results, students’ motivation majoring in English education IAIN Surakarta has shown good motivation. Of the four aspects in the analysis, it can be seen that the students have a good motivation. In the aspect of integrative, most of the students already have a good attitude towards learning English. It can be seen from the statistics obtained from questionnaires given. Statistics show that as many as 34.46% of the students agreed and 38.21% strongly agreed. The instrumental aspect also shows quite positive results. This can be proven by statistics that more than 41% of students answered agree to the statements in the questionnaire given. On the attitude towards lecturers, data obtained from quetionaire showed that 39.17% of the students agreed and 10:42% of respondents strongly agreed with the statement given. The last is a question related to the subject, as many as seven out of ten statements contained in this aspect of this course is a negative statement. So it can be concluded that the students already have a good attitude and interest towards learning English. From the statistics above show that student majoring in English education IAIN Surakarta had a pretty good motivation to learn, but still need for development in order to reach optimal learning results.